The Mediating Role of User Satisfaction in the Relationship Between Information Systems Service Quality and Individual Performance in Malang University-Level e-Learning - Nur Prima Waluyowati; Muhammad Hafiz Riandi (Jurnal Manajemen dan Kewirausahaan, 2024)
This research investigates the multifaceted landscape of online education for students of higher education within Malang City, Indonesia. In today's digital learning era, the quality of Information System Service in online educational platforms stands as a critical factor. This study extends its scope beyond a straightforward examination of the direct relationship between Information Systems Service Quality and User Satisfaction Â by introducing Individual Performance Â as the final dependent variable, rendering User Satisfaction to be a mediating variable. Through meticulous quantitative analysis employing SmartPLS 3.0, this study unravels the fact that User Satisfaction emerges as a complement partial mediating agent, positively influencing the association between Information Systems Service Quality and Individual Performance for higher education students in Malang. This underscores the role of contented students in amplifying the positive effects of Information Systems Service Quality on their academic achievements. Beyond contributing to the comprehension of online education, this research holds substantial implications for educational institutions and policymakers. It underscores the necessity of adopting a comprehensive approach that intertwines Information Systems Service Quality and Student Satisfaction to foster successful and satisfied online learners, not only in Malang City but also in broader contexts.